1997
DOI: 10.1523/jneurosci.17-12-04633.1997
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility to Neurotoxicity Mediated by Neurotrophins and Neuronal Nitric Oxide Synthase

Abstract: NMDA neurotoxicity, which is mediated, in part, by formation of nitric oxide (NO) via activation of neuronal NO synthase (nNOS), is modulated by neurotrophins. nNOS expression in rat and mouse primary neuronal cultures grown on a glial feeder layer is significantly less than that of neurons grown on a polyornithine (Poly-O) matrix. Neurotrophins markedly increase the number of nNOS neurons, nNOS protein, and NOS catalytic activity and enhance NMDA neurotoxicity via NO-dependent mechanisms when neurons are grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 78 publications
4
61
0
Order By: Relevance
“…In vivo models of cerebral ischemic preconditioning also do not support NMDA receptor-mediated production of nitric oxide (17,46). Possible reasons cited for negligible neuronal NOS expression in cortical culture (54), such as plating neurons on an established glial bed, cannot account for this discrepancy in the present cultures.…”
Section: Nitric Oxide-independent Preconditioningmentioning
confidence: 65%
“…In vivo models of cerebral ischemic preconditioning also do not support NMDA receptor-mediated production of nitric oxide (17,46). Possible reasons cited for negligible neuronal NOS expression in cortical culture (54), such as plating neurons on an established glial bed, cannot account for this discrepancy in the present cultures.…”
Section: Nitric Oxide-independent Preconditioningmentioning
confidence: 65%
“…Marmigere et al, 2003), whereas LPS and stress activate glutamatergic (Karreman and Moghaddam, 1996;Glezer et al, 2003) and dopaminergic (Abekawa et al, 2000;Gamaro et al, 2003;Matsumoto et al, 2005) systems, which induces BDNF expression (Zafra et al, 1990(Zafra et al, , 1991Kuppers and Beyer, 2001). Although BDNF increases in pathological situations (Felderhoff-Mueser et al, 2002) and seems to exert a protective activity (TapiaArancibia et al, 2004), some evidence suggests that neurotrophins strengthen or may even cause neuronal damage under certain pathological conditions through the induction of NADPH-oxidase (Koh et al, 1995;Samdani et al, 1997;Kim et al, 2002). Thus, BDNF could be involved in the increase of the damage induced by inflammation in stressed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus arises the question of how to reconcile the neuroprotective effect of activating p44͞42 MAP kinase reported in previous studies with the neuroprotective effect of inhibiting p44͞42 MAP kinase reported here. The finding that neurotrophins can exacerbate neuronal death under some circumstances may be relevant to this question (53)(54)(55). Neurotrophins protect cultured cortical neurons against apoptotic death induced by serum withdrawal, but in the same system, neurotrophins exacerbate necrotic death induced by either glucose-oxygen deprivation or the brief application of N-methyl-D-aspartate (54).…”
Section: Discussionmentioning
confidence: 99%